Transorbital ultrasound in the diagnosis of giant cell arteritis - Petzinna, Simon M; Burg, Lara C; Bauer, Claus-Juergen; Karakostas, Pantelis; Terheyden, Jan H; Behning, Charlotte; Holz, Frank G; Brossart, Peter; Finger, Robert P; Schäfer, Valentin S (Rheumatology (Oxford, England), 2024)
The objective of this study was to prospectively evaluate the diagnostic efficacy of transorbital ultrasound (TOS) in patients newly diagnosed with giant cell arteritis (GCA), presenting with visual symptoms. Patients with newly diagnosed, untreated GCA were examined using TOS, assessing central retinal artery flow velocity [peak systolic velocity (PSV), end-diastolic velocity (EDV), resistance index (RI)], and optic nerve diameter (OND). Vascular ultrasound was conducted to evaluate the superficial temporal arteries, their branches, facial, axillary, carotid, and vertebral arteries. We enrolled 54 GCA patients, 27 with visual symptoms, and 27 healthy controls. Eyes of GCA patients with visual symptoms demonstrated significantly lower PSV and EDV (PSV: β = -1.91; P = 0.029; EDV: β = -0.57; P = 0.032) and significantly elevated OND (β = 0.79; P = 0.003) compared with controls. RI did not significantly differ from controls (β = -0.06, P = 0.129). Vascular ultrasound identified an average of 8.7 (SD ± 2.8) pathological vessels per GCA patient. A significant negative association was observed between the number of affected vessels and both PSV (P = 0.048) and EDV (P = 0.040). No association was found with RI (P = 0.249), while a positive significant association was noted with OND (P < 0.001). This study pioneers the application of TOS to assess structural eye changes in newly diagnosed, untreated GCA patients with visual symptoms. Our findings suggest reduced central retinal artery flow and increased optic nerve diameter as potential biomarkers for serious ocular involvement in GCA. The detected association between internal and external carotid artery involvement indicates a common pathophysiological mechanism underlying systemic and ocular manifestations of GCA.